Efficiency of World Ports in Container and Bulk Cargo (oil, coal, ores and grain) - Merk, Olaf (OECD Regional Development Working Papers, 2012)
Port efficiency is an important indicator of port performance; more efficient ports lower transportation costs and facilitate imports and exports of a country. Despite the importance of the subject, the exisiting port efficiency studies have almost exclusively focused on container ports. This Working Paper aims to fill that gap by calculating efficiency scores of world ports per cargo type (containers, oil, coal, iron ore and grain). These calculcations have been made using a database constructed for this purpose. Several findings can be derived from these calculations. Significant improvements can be made when the technical efficiency of ports is increased. Among the sample, gaps between terminal efficiency mostly reflected gaps in pure technical efficiency. When comparing the level of efficiency achieved by ports across commodities, technical gaps were more marked for container and oil terminals.